Bringing rights into resilience: revealing complexities of climate risks and social conflict. (6th August 2018) - Ensor, Jonathan; Forrester, John; Matin, Nilufar
Abstract : Marginalisation and exclusion are expressed in social conflict and are determinative in distributing risk and resilience. This paper builds on recent literature that has adopted a human rights lens to explore how resilience practice can better account for issues of equity and power. Using the illustrative case of Timor‐Leste, it presents an analysis of how human rights principles play out in the settings in which rights are given meaning. The approach reveals the reproduction of patterns of conflict and risk, and suggests two key priorities for resilience practice: first, recognising and responding to the deep‐rooted narratives and procedures that normalise inequality and marginalisation at different scales; and second, allowing for transformation towards more equitable political and social arrangements as a part of resilience practice. Augmenting resilience with rights‐based thinking can situate resilience practice, such that it responds to the complexity of social arrangements, reducing risk and social conflict.